2017
DOI: 10.1002/ijc.31182
|View full text |Cite
|
Sign up to set email alerts
|

Integrating expression‐related SNPs into genome‐wide gene‐ and pathway‐based analyses identified novel lung cancer susceptibility genes

Abstract: Traditional pathway analysis map single nucleotide polymorphisms (SNPs) to genes according to physical position, which lacks sufficient biological bases. Here, we incorporated genetics of gene expression into gene- and pathway-based analysis to identify genes and pathways associated with lung cancer risk. We identified expression-related SNPs (eSNPs) in lung tissues and integrated these eSNPs into three lung cancer genome-wide association studies (GWASs), including 12,843 lung cancer cases and 12,639 controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…SKAT is a powerful approach to identify phenotype-related regions (for example, genes and other moving windows across the genome) by combining the effects of both common and rare variants in the same region. This method has been widely applied in previous studies and multiple novel traitrelated genes were successfully identified, including novel oncogenes in lung cancer (21)(22)(23).…”
Section: Motif-based Analysismentioning
confidence: 99%
“…SKAT is a powerful approach to identify phenotype-related regions (for example, genes and other moving windows across the genome) by combining the effects of both common and rare variants in the same region. This method has been widely applied in previous studies and multiple novel traitrelated genes were successfully identified, including novel oncogenes in lung cancer (21)(22)(23).…”
Section: Motif-based Analysismentioning
confidence: 99%
“…In conclusion, the traditional method of finding disease markers is mostly dependent on the expression level of single genes. The assumption is that each gene is relatively independent, so the doctor will use the selected gene’s characteristics to design diagnostic kits, make the combination of chips or sequencing, and predict the risk of illness based on gene expression [ 9 ]. However, in organisms, the gene is not relatively independent, and there is a functional interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that expression of MPZL3 is associated with different cancer types. A previous study reports that MPZL3 is a associated with lung cancer susceptibility 22 . A study on microarray analysis showed that MPZL3 is highly expressed in rectal cancer cells 23 .…”
Section: Discussionmentioning
confidence: 97%